Two new vertebrate prey species in the diet of the agouti, Dasyprocta punctata, recorded in the highlands of Costa Rica - Mora, José Manuel; Castrillo Trejos, Andrey; Méndez Vargas, Esteban; Castro Arias, Rony; López, Lucía I. (Therya Notes, 2024)
The Central American agouti, Dasyprocta punctata, has traditionally been considered an herbivore, primarily feeding on fruits and seeds. However, there are reports of this rodent consuming 3 vertebrate species: a mouse (in captivity), a bird, and a worm lizard. In this study, we add 2 new vertebrate species to the diet of the agouti: a bird and a mammal. We conducted research and led natural history tours in the Monteverde region of Costa Rica. Monteverde is well-known for its biological reserves and ecotourism activities. The villages of Monteverde and Santa Elena are situated within the Tropical Montane Cloud Forest, a relatively narrow elevational band with frequent cloud cover throughout much of the year. On 2 separate occasions, we observed agoutis preying on vertebrate species in Monteverde. On June 8, 2023, we saw an adult agouti with a juvenile nine-banded armadillo, Dasypus novemcinctus, in its mouth. On July 12, 2024, we observed another agouti pursuing and consuming 2 chicks of the black-breasted wood-quail, Odontophorus leucolaemus. These 2 new prey items suggest the opportunistic carnivorous tendencies of the agouti. It appears to capture young animals that do not pose a significant threat or require considerable effort to catch, nor do they cause collateral damage. In this way, the agouti obtains some essential nutrients that it does not get from its usual plant-based diet during lean times.